Covid-19 Pandemic, Personal Hygiene and Dietary Behavior of Ghanaians: From the Perspective of Inhabitants of Burma Camp, Accra - Osei-Brobby, Jessie; Odoom, Daniel; Opoku, Mensah Eric; Dick-Sagoe, Christopher (African Journals Online (Lwati: A Journal of Contemporary Research), 2022)
COVID-19 has affected various aspects of life including education and health. This study examined how the pandemic has affected dietary behavior and personal hygiene of people in a descriptive survey. The study was underpinned by the human capital and social learning theories. A total of 133 inhabitants of Burma Camp who were conveniently selected responded to a set of questionnaire. Analytical techniques employed in the study included means, standard deviation and regression. The study found that COVID-19 has affected dietary behavior of people in many ways including paying much attention to their dietary behavior, not eating outside food, often eating warm food, and taking Vitamin C supplements. However, COVID-19 pandemic has not reduced consumption of alcohol, consumption of canned fruit juice, and overall consumption of canned foods. Again, because of the pandemic people now take their personal hygiene seriously, frequently use alcohol based hand sanitizer, wash their hands with soap routinely, observe physical distance at public places, and avoid crowded places. The regression analysis confirmed that COVID-19 has an effect on the dietary behavior and personal hygiene of inhabitants at Burma Camp. The findings have also been discussed in the context of their value for theoretical literature. As a way of recommendation, inhabitants are encouraged to continue to take their dietary behaviors and personal hygiene seriously so as to stay healthy amidst the spread of the virus.
Research Article
Keywords: Covid-19 Pandemic, Personal Hygiene, Dietary Behavior, Ghana, Burma Camp, Accra